2022
DOI: 10.1186/s13005-022-00330-5
|View full text |Cite
|
Sign up to set email alerts
|

Remineralization and protection from demineralization: effects of a hydroxyapatite-containing, a fluoride-containing and a fluoride- and hydroxyapatite-free toothpaste on human enamel in vitro

Abstract: Background The aim was to evaluate the remineralization potential as well as the extent of protection against renewed demineralization of enamel by hydroxyapatite-containing toothpaste (Karex) in comparison to fluoride-containing (Elmex) and fluoride- and hydroxyapatite-free toothpaste (Ajona) as control. Methods Fifty-seven enamel samples were obtained from 19 human teeth. Five demarcated surfaces were created on each tooth (S0—S4). Four of the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…However, its independent protective effect against erosion is not yet clearly defined 15 . Hydroxyapatite-containing toothpaste showed the lowest percentage of remineralization and protection effect against subsequent demineralization compared to AmF-containing toothpaste and fluoride- and hydroxyapatite-free toothpastes 16 . nHA also showed the least remineralizing properties compared to CPP-ACPF and bioactive glass on eroded enamel lesions 14 .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, its independent protective effect against erosion is not yet clearly defined 15 . Hydroxyapatite-containing toothpaste showed the lowest percentage of remineralization and protection effect against subsequent demineralization compared to AmF-containing toothpaste and fluoride- and hydroxyapatite-free toothpastes 16 . nHA also showed the least remineralizing properties compared to CPP-ACPF and bioactive glass on eroded enamel lesions 14 .…”
Section: Introductionmentioning
confidence: 88%
“…Various compounds, including fluoride 3 , 7 , 9 – 11 , casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) 11 – 14 , nanohydroxyapatite (nHA) 11 , 14 – 16 , chitosan 17 , 18 , and protease inhibitors 7 , 19 have been used in the forms of toothpaste, mouth rinse, gel, and varnish to prevent tooth erosion progression and alleviate hypersensitivity. Different forms of fluoride, including sodium fluoride (NaF), amine fluoride (AmF), monofluorophosphate (MFP), and stannous fluoride (SnF 2 ) with different concentrations and pH levels, have demonstrated a significant reduction in enamel dissolution and an increase in resistance to acid attacks by deposition of protective calcium fluoride layer on the tooth surface 9 .…”
Section: Introductionmentioning
confidence: 99%
“…For hardness measurements, a section was made in the center of each block, and one of the halves was embedded in acrylic resin and gradually polished. One sequence of 14 indentations was created at different distances (5,10,15,20,25,30,40,50,70,90,110,130,220, and 330 μm) from the surface of the enamel, in the central region of the blocks, using a Micromet 5114 hardness tester (Buehler ) with a Knoop diamond indenter under a 5 g load for 10 s. Integrated hardness (KHN × μm) for the lesion into sound enamel was calculated by the trapezoidal rule (GraphPad Prism, version 3.02) and subtracted from the integrated hardness for sound enamel to obtain the integrated area of the subsurface regions in the enamel, obtaining the integrated loss of subsurface hardness (∆KHN; KHN × μm). 9,22 Analysis of the profile and depth of subsurface lesions using polarized light microscopy After cross-sectional hardness analysis, the enamel blocks (n = 12/group) embedded in acrilyc resin were sectioned to obtain slices of 300 µm and ground to a thickness of ~100 um using 400 grit paper (Paper Discs,30-5108-320, Buehler) at grinder polisher (Phoenix Beta with Vector Powerhead, Buehler), under constant water refrigeration.…”
Section: Analysis Of Enamel Hardnessmentioning
confidence: 99%
“…4 Thus, it functions as a source of F, thereby interfering with the dynamics of the de-remineralization processes. 5 To maximize the clinical significance of remineralization, a number of preventive agents in some studies have shown successes in using P, Ca ions associated with F on the tooth surface, assisting in enamel remineralization. 3,6,7 The performance of dairy products, as a topical anticariogenic effect, has been noted since the 1980s.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies suggest that fluoride (F) remains the best established agent to promote remineralization [ 8 , 9 ]. This is attributed both to the fluoride-enhanced precipitation into the tooth enamel of Ca 2+/ PO 4 3− and to the formation of fluorohydroxyapatite (F-HA) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%